2019
DOI: 10.3389/fimmu.2019.02454
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the CDR Loops of Antigen Receptors

Abstract: The adaptive immune system uses two main types of antigen receptors: T-cell receptors (TCRs) and antibodies. While both proteins share a globally similar β-sandwich architecture, TCRs are specialized to recognize peptide antigens in the binding groove of the major histocompatibility complex, while antibodies can bind an almost infinite range of molecules. For both proteins, the main determinants of target recognition are the complementarity-determining region (CDR) loops. Five of the six CDRs adopt a limited n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…Additionally, a characterization of structure and dynamics of a TCR is essential to elucidate the antigen-binding mechanism, the involved conformational changes and the associated biological implications ( 4 , 17 , 18 ). X-ray studies comparing TCRs crystallized with and without the pMHC complex revealed a high flexibility in the binding interface ( 1 , 3 , 14 , 17 , 20 ). However, crystal structures represent only a snapshot of a specific protein conformation that can be distorted due to crystal packing effects ( 15 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, a characterization of structure and dynamics of a TCR is essential to elucidate the antigen-binding mechanism, the involved conformational changes and the associated biological implications ( 4 , 17 , 18 ). X-ray studies comparing TCRs crystallized with and without the pMHC complex revealed a high flexibility in the binding interface ( 1 , 3 , 14 , 17 , 20 ). However, crystal structures represent only a snapshot of a specific protein conformation that can be distorted due to crystal packing effects ( 15 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of the T-cell the TCR is expressed on, it recognizes protein fragments derived from intra- or extracellular regions, displayed by the Major Histocompatibility Complex (MHC) ( 2 ). TCRs consist of an α and a β chain analogous to the heavy and light chain in the antigen-binding fragment (Fab) of antibodies ( 3 , 4 ). Vα and Cα can be interpreted as homologous in sequence and structure to the V L and C L domains in antibodies as well as Vβ and Cβ as equivalent to V H and C H ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 30% of pro-Abs did not achieve the blocking ability to even 50-fold compared to parental Abs. The reason for the low blocking ability is that there are distinct differences among the complementarity-determining region (CDR) loop of each Ab, [20,21] so the identical linker of the Ab lock cannot be applied to every Ab. In order to overcome this issue, it is essential to design a method to predict and optimize the Ab lock with a suitable linker for each Ab.…”
Section: Introductionmentioning
confidence: 99%